Spring-Back Characteristics on Bent Holed Parts in V-Die Bending Process - Sutasn Thipprakmas; Arkarapon Sontamino (Advances in Materials Science and Engineering)
In recent years, the bending of holed blank to fabricate the bent holed parts has been increasingly applied in almost all industrial fields and they also need much more complexity in shaped part and precision in dimensions. However, most of past research studies were carried out on bent nonholed parts. This causes an insufficient database and information for die design to fabricate bent holed parts. In the present research, to achieve a good design of V-bending die for fabrication of these bent holed parts, the bending mechanism and spring-back characteristic were clearly clarified based on experimental works. By making hole, it usually caused the decreases in generated bending characteristic on bending allowance zone as the hole located at center as well as the decreases in the generated reversed bending characteristics on next to bending allowance zone as the hole located next to bending allowance zone. The hole also caused the increases in additional elastic zone on hole especially for hole located at center due to the hole distortion during bending process. The effects of hole diameter were also investigated. The results elucidated that the larger hole diameter applied, the larger amount of spring-back obtained. Therefore, to achieve a good design of V-bending die for fabrication of V-bent parts of holed blank, the hole position and diameter should be carefully considered.